Les modalités de gestion et d’entretien des parcs publics en Tunisie - Besma Loukil; Taoufik Bettaieb; Pierre Donadieu (Projets de Paysage)
In this paper we are explaining the noticed fluctuations in management of public spaces such as urban parks. First of all, we treat the constraints met by the actors of the management. Some constraints are due to the user’s behavior. Then, we illustrate the role of the public policy and its effect on management practices directly through the financing and indirectly through creation and distribution of these spaces within the urban environment. Finally, the present text shows the adding value of private companies and international cooperations to the quality of the contribution in the management of parks and public gardens.